Pengembangan Sistem Rekomendasi Produk Perawatan Kulit Berbasis Web Menggunakan Metode AHP - Jojor Yeanesy Sinaga; Faizatul Amalia; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Skin is one of the largest organs in humans. In order to carry out these functions, the skin must be properly guarded and cared for. Especially on facial skin. Besides being able to attract attention, beautiful and healthy facial skin can also increase self-confidence. Choosing facial skin care products should not be arbitrary because it can cause the skin to become irritated and dehydrated. It is very important to see if the skin and problems are first. However, in fact there are still many who choose the wrong care products. Based on these problems, a system of recommendations for skin care products was developed based on skin types and web-based skin problems. To get recommendations, the method used is AnalyticaI Hierarchy Process (AHP). The system development process is carried out using the waterfall method with an Object-Oriented (OO) approach and web-based. Testing on functional requirements is carried out by unit testing and validation. The results obtained are 100% valid in all tested cases. Testing on non-functional requirements is carried out with compatibility testing and the results obtained indicate that the system can be accessed from various browsers and different operating systems. Testing the recommendation method performed with accuracy testing produces a value of 66.67%. The results obtained indicate the system can function properly according to the AnalyticaI Hierarchy Process (AHP) method.